All Themes from Young Goodman Brown by Nathaniel Hawthorne - Girsang, Martina; Silalahi, Rachael Joy Nabasa (Jurnal Riset Ilmu Pendidikan, 2025)
In "Young Goodman Brown," Goodman Brown, is a young man who leaves his wife, Faith, and ventures into the forest one night, despite her pleas for him to stay. In the forest, he meets a mysterious old man who turns out to be the devil. The devil leads him to a gathering where Goodman Brown witnesses respected members of his community, including his minister and his wife, participating in a satanic ritual. This revelation shatters Goodman Brown’s perception of the world and his faith in others. He becomes disillusioned and loses trust in everyone, including Faith, whom he had once cherished. At the end of story, he returns to his village, a changed man, distrustful and disconnected from those around him. The story explores themes of faith, temptation, loss of faith or innocence, and etc. In this article the author wants to present the elements of fictional prose, especially the themes that are at the core of the story, through various sources obtained.